Developing a Bookless Library for Enhanced Literacy in Islamic Boarding Schools - Musthofa, Hamsyah; Haryanto , Budi (Indonesian Journal of Islamic Studies, 2024)
Abstract: The 4.0 industrial revolution compels educational institutions, including Islamic boarding schools, to adopt advanced digital library services for enhanced literacy. General Background: Many libraries, such as that of Al Fattah Islamic Boarding School in Sidoarjo, still depend on physical books and lack accreditation, resulting in outdated collections. Specific Background: There is a significant gap in structured digital library frameworks that provide extensive access to both general and Islamic literature. Aims: This study aims to develop a school development plan for a Bookless Library that enhances digital literacy. Results: Employing a Research and Development (R&D) approach, the study outlines a five-year strategic plan for implementing a digital library, utilizing QR codes for quick access to resources. Novelty: It proposes a global access model for the Bookless Library, allowing users beyond the server's immediate area to engage with digital resources. Implications: The expected outcome is a dynamic learning environment that promotes literacy and positions Al Fattah Islamic Boarding School competitively in a technology-driven educational landscape. Highlights: Technological Adaptation: The implementation of digital libraries addresses the evolving needs of students in the 4.0 industrial revolution. Resource Accessibility: QR codes facilitate instant access to a vast array of digital resources, enhancing learning opportunities. Global Reach: The proposed Bookless Library model allows users beyond local boundaries to engage with diverse literature. Keywords: Digital Library, Bookless Library, Islamic Boarding School, Literacy Enhancement, Research and Development